Penggunaan Sistem Microcontroler Untuk Penyiraman Tanaman Secara Terjadwal Menggunakan Arduino - Ardana, Fath Arya; Suhada, Suhada; Damanik, Bahrudi Efendi (TIN: Terapan Informatika Nusantara, 2021)
So far, watering plants is done manually. However, sometimes humans are constrained by limited free time. By using this tool, it is expected that watering the plants can be done at the right time. This research was conducted by making a device that can water plants on a scheduled basis using the Real Time Clock Module which is controlled by Arduino Uno. Plant watering system that is made can water plants automatically according to the schedule that has been set. The results of this study aim to facilitate the process of watering plants in the yard